2017
DOI: 10.2172/1353014
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hanford Cast Stone Supplemental LAW using Composition Adjusted SRS Tank 50 Salt Solution

Abstract: Vitrification is the primary disposition path for Low Activity Waste (LAW) at the Department of Energy (DOE) Hanford Site. A cementitious waste form is one of the alternatives being considered for the supplemental immobilization of the LAW that will not be treated by the primary vitrification facility. Washington River Protection Solutions (WRPS) has been directed to generate and collect data on cementitious or pozzolanic waste forms such as Cast Stone. This report documents work done to support supplemental i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…Semi-dynamic leach testing of the AgZ containing wasteforms showed that in an oxidized formulation (no blast furnace slag included), no iodine was detected in the resulting leachates. This measurement was similar to another test where 5 mass% AgZ was added to a cementitious wasteform for iodine in liquid waste and on stabilizing silver alumina, silver silica gel, and AgZ in Portland cement (Mizuno et al, 1986;Lockrem, 2005;Crawford et al, 2017). This enhanced iodine retention was attributed to an Aglayer that was observed to form at the interface between the AgZ particle and matrix, see Figure 5.…”
Section: Low-temperature Hydrating or Polymerizing Wasteformssupporting
confidence: 78%
“…Semi-dynamic leach testing of the AgZ containing wasteforms showed that in an oxidized formulation (no blast furnace slag included), no iodine was detected in the resulting leachates. This measurement was similar to another test where 5 mass% AgZ was added to a cementitious wasteform for iodine in liquid waste and on stabilizing silver alumina, silver silica gel, and AgZ in Portland cement (Mizuno et al, 1986;Lockrem, 2005;Crawford et al, 2017). This enhanced iodine retention was attributed to an Aglayer that was observed to form at the interface between the AgZ particle and matrix, see Figure 5.…”
Section: Low-temperature Hydrating or Polymerizing Wasteformssupporting
confidence: 78%
“…Similar to testing of 99 Tc leaching from grout, observed diffusivity for 129 I was determined for each time interval during the EPA 1315 leach testing. Figure 15(b) compares the results for the two grouts in this study and with previously reported work in Asmussen et al (2019) and Crawford et al (2017). Again, the UHPG had much lower observed diffusivity than the Baseline grout.…”
Section: I Leaching From Groutsupporting
confidence: 70%
“…Observed diffusivity for 99 Tc was determined for each time interval during the EPA 1315 leach test using results from the analysis of leachate samples. Figure 15 (a) compares the results for the two grouts in this study and with work previously reported by Crawford et al (2017) Crawford et al (2017 present results from testing of grout prepared using the caststone (CS) recipe and Tank 50 liquid radioactive waste which contains a variety of radionuclides including 99 Tc and is characterized by high ionic strength and pH >14 resulting from the addition of NaOH to prevent corrosion. The UHPG had much lower observed diffusivity for both the Baseline grout was likely due to the lower porosity, Figure 8, and pore connectivity of the UHPG as shown by porosity and water retention characteristics (Figure 10 and Figure 11) as well as the ks limitations.…”
Section: Tc Leaching From Groutmentioning
confidence: 61%